Sex trafficking and moral harm: politicised understandings and depictions of the trafficked experience - O'Brien, Erin E. (Critical criminology, 2013)
This paper explores notions of harm in sex work discourse, highlighting the extent to which essentialist ideas of ‘good’ versus ‘bad’ sex have pervaded trafficking policy. In a comparative examination of Australian Parliamentary Inquiries and United States congressional hearings leading to the establishment of anti-trafficking policy, we identify the stories that have influenced legislators, and established a narrative of trafficking heavily dependent upon assumptions of the inherent harm of sex work. This narrative constructs a hierarchy of victimisation, which denies alternative discourses of why women migrate for sex work. We argue that it is not sexual commerce that is harmful, but pathological, systemic inequalities and entrenched disadvantage that are harmful. A narrow narrative of trafficking fails to adequately depict this complexity of the trafficked experience.